Factors associated with mortality among inpatients at Koidu Government Hospital, Sierra Leone: A Secondary data analysis - Ivan Augustine Barrie; Solomon Aiah Sogbeh; Babatunde Duduyemi; Umaru Sesay; Amara Alhaji Sheriff; Anna Jammeh; Adel Hussein Elduma; Gebrekrstos Negash Gebru (Journal of Interventional Epidemiology and Public Health)
Introduction: Sierra Leone's life expectancy in 2019 was 61 years, below the average for low-income African countries. This study aimed to determine factors associated with morbidity and mortality among inpatients at Koidu Government Hospital (KGH), addressing limited data on hospital outcomes in Sierra Leone.